PERTOBATAN MENURUT UMAT STASI SANTA MARIA KOLONG BOJONEGORO DITINJAU DARI PENGALAMAN PERTOBATAN SANTO PAULUS - Cornelius Triwidya Tjahja Utama; Destara Yulius Andriansyah (Bahasa Indonesia, 2018)
Everyone has their own way in many respects, specifically related to the repentance. Basically all persons called by God through his conviction. Catholics are called by God to continually renew themselves through repentance in order to free themselves from the slavery of sin, aimed to reorient his mind and entire life to God and to toward the way of the Lord. Majority of St. Mary Christian community composed of the farmers. In the beginning, the number of Christian faithful in the community was very small. Saint Paul was a Pharisee who was really hating very much Christ, even he did the hard and cruel actions of the followers of Christ. However he was then called by God to become a special follower of Christ. Paul preached the Gospel with his own which attacted a lot of people to become Christians. There are similarities regandiog the experience of repentance between Catholics in St. Mary communitity Stasi with St. Paul. This study uses qualitative research conducted with individual interviews. From the research results can be concluded that respondents understand the meaning of repentance. They experience the feel called to repent. About the benefits of the respondents said that being more responsible for the family and his job. Regarding the spirit of repentance says seriously repented, and the impact they want to be like St. Paul. They are very keen to repent. the impact Paul realized his sin. Respondents are motivated to explore the teaching of St. Paul.